SOCIO-DEMOGRAPHIC DETERMINANTS OF SMALL SCALE FARMERS’ LAND TENURE SYSTEM IN KWARA STATE - Oluwafemi Oyedeji; Esther Awotunde; Ezekiel Ojediran; Segun Fakayode (Journal of Agribusiness and Rural Development, 2018)
This study examined the socio-demographic determinantsof the type of land tenure system used by smallfarmers in Kwara State, Nigeria. A two-stage sampling techniquewas used to collect data from ninety six farmers for thepurpose of this study. Once collected, the data was analyzedusing both descriptive statistics and a multinomial regressionmodel. The results of the analysis show that 72.92% of the respondentsare married, 75% are males, 39.58% are aged above40, 52.08% own 6–10 acres of land, and 75% acquired theirland through inheritance. The result of the multinomial regressionanalysis shows that household size, the farmer’s age, genderand marital status, number of farms, farm size, educationlevel and land use type were the key determinants for the typeof land tenure system used in the study area. The study concludedthat most respondents have access to farmland eitherby inheritance or purchase, as determined by their age, gender,household size and level of education. This study thereforerecommends that farmland leasing should be encouraged especiallyfor abandoned inherited farmland, so as to put it intoproductive agricultural use.